No way of knowing : crime, urban legends, and the Internet - Donovan, Pamela (American popular history and culture (Routledge (Firm)), 2004)
This volume examines both 'old media' treatment of crime legends: news reports, fictional film and television depictions, as well as 'new media' interactive discussions of them: versions and discussions circulating in Internet newsgroups and via electronic mail lists.